The Legal Status of General Practitioners at the dawn of the New Primary Care in Italy - Vinceti, S. R. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
A debate is developing in Italy on the reform of the employment status of general practitioners. The dispute was prompted by the extraordinary resources the European Union has allocated to Italy on the condition of several structural reforms, among which lies the renewal of the primary care system. One of the most debated questions is whether general practitioners should become civil servants or remain autonomous workers. The issue is not only relevant to the quality and efficiency of primary care but is propitious for improving the legal certainty of this “hybrid figure” in Italian health law. The commentary suggests that, from a public law point of view, the employment status of civil servants better agrees with the foreseeable conditions of general practitioners working in Community Houses. In any case, national and regional policymakers must take into consideration possible controversies and litigation arising from an inappropriate qualification of the legal status of general practitioners in building the new system of Italian primary care.